OPTIMALISASI PUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DALAM KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN KERINCI - Mahyudi Mahyudi; Ferdi Ferdi (UNES Journal of Swara Justisia, 2017)
PBB-P2 is a tax whose delegated authority is transferred to the Regency / City Government. Kerinci Regency Government began applying the Land and Rural Land and Urban Tax collection from January 1, 2014. This research was conducted to find out how the implementation of tax collection of earth and rural and urban buildings in Detailed District and to find out how its contribution to the original revenue area in Kerinci regency. This research uses primary data in the form of interview result as main data, and secondary data as supporter. Based on the result of this research, it is found that the taxation of earth and rural and urban building in Kerinci Regency has not run optimally, because the officer has not consistently run the regulation, so that its contribution to the local revenue is not optimal only about 1.23% in 2014 and 1.19 % By 2015.